2011
DOI: 10.1016/j.jpurol.2011.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results with a one-stage complex primary hypospadias repair strategy (the three-in-one technique)

Abstract: The one-step strategy is associated with 68.5% success in a single operation, whereas 31.5% will need a second repair. We recognize that meatal problems are mostly associated with fistulae and diverticula; therefore, we recommend a final acceptable proximal glandar opening that will not compromise the neourethra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
0
5
0
1
Order By: Relevance
“…Newer approaches to onlay grafting, such as the widely anchored patch recently suggested by Djordjevic and colleagues may improve the results of a 1-stage approach for these complicated patients [21]. Thus far, we have found buccal mucosal grafting to be unnecessary for primary hypospadias repairs, although other authors have reported success with this technique for cases of hypospadias with severe chordee [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Newer approaches to onlay grafting, such as the widely anchored patch recently suggested by Djordjevic and colleagues may improve the results of a 1-stage approach for these complicated patients [21]. Thus far, we have found buccal mucosal grafting to be unnecessary for primary hypospadias repairs, although other authors have reported success with this technique for cases of hypospadias with severe chordee [22]. …”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of exploration of one-stage reconstruction using tubularized graft. In some cases, onlay grafts may not be suitable and tubularized urethroplasty is necessary [20,21]. We previously performed urethroplasty in a rabbit model with saphenous vein patch as onlay graft and gained encouraging results [7].…”
Section: Discussionmentioning
confidence: 99%
“…Macedo et al [29] described the ‘three-in-one’ technique using buccal mucosa, an onlay with a vertical skin flap, and a tunica vaginalis cover, in 40 children. The complication rate was 37%, including four with meatal stenosis, four with a diverticulum, five with fistula, two with residual curvature and two with recurrent UTIs, with a re-operative rate of only 31.5% for a second surgery.…”
Section: Discussionmentioning
confidence: 99%